2021
DOI: 10.1007/s10948-021-05994-9
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity with Topological Non-trivial Surface States in NbC

Abstract: Quantum materials with non-trivial band topology and bulk superconductivity are considered superior materials to realize topological superconductivity. In this regard, we report detailed Density Functional Theory (DFT) calculations for NbC superconductor which shows the topologically non-trivial band structure. Bulk superconductivity at 8.9K is confirmed through DC magnetization measurements under Field Cooled (FC) and Zero Field Cooled (ZFC) protocols. This superconductivity is found to be of type-II nature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Both NbC and TaC show superconductivity at relatively higher temperature which are 11.5K and 10.5K respectively [92][93][94][95][96][97]. These materials are found to have a type-II Dirac semimetal like band structure, which has been confirmed through both DFT calculations and ARPES measurements [93][94][95][96][97].…”
Section:  Centrosymmetric Superconductorsmentioning
confidence: 91%
See 3 more Smart Citations
“…Both NbC and TaC show superconductivity at relatively higher temperature which are 11.5K and 10.5K respectively [92][93][94][95][96][97]. These materials are found to have a type-II Dirac semimetal like band structure, which has been confirmed through both DFT calculations and ARPES measurements [93][94][95][96][97].…”
Section:  Centrosymmetric Superconductorsmentioning
confidence: 91%
“…Other examples of centrosymmetric superconductors, which are supposed to show topological superconductivity, are transition metal carbides (TMCs) viz. NbC and TaC [92][93][94][95][96][97].…”
Section:  Centrosymmetric Superconductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The general experiment-detected Young's moduli were B537 GPa for TaC [26][27][28] and B493 GPa for NbC, 29,30 which can be explained by the bonding characters between the d orbitals of transition metal atoms and p orbitals of carbon atoms. Besides, NaCl-type TaC and NbC show superconductivity at a critical temperature in the range of 8 to 11 K. [31][32][33][34][35] Recently, several different research groups reported the topological properties and the nodal line characteristic in rocksalt-type NbC, 36,37 while another group reported NbC as a Dirac semimetal by combining theoretical calculations and angle resolved photoemission spectroscopy (ARPES) measurements. 34 In addition, the isostructural TaC is proposed as a topological superconductor candidate.…”
Section: Introductionmentioning
confidence: 99%